2013
DOI: 10.1063/1.4807137
|View full text |Cite
|
Sign up to set email alerts
|

High quality factor nonpolar GaN photonic crystal nanocavities

Abstract: High quality factor a-plane nonpolar GaN two-dimensional photonic crystal (PC) nanocavities on r-plane sapphire substrates have been demonstrated. Nonpolar GaN PC nanocavities on a thin membrane structure were realized by using e-beam lithography to define the PC patterns and focused-ion beam milling to fabricate the suspended thin membrane. A dominant resonant mode at 388 nm with a high quality factor of approximately 4300 has been demonstrated at 77 K by the micro-photoluminescence system. Moreover, the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…It was found that the fabricated membranes exhibit resonant modes with Q = 300, and it was suggested that further design and process optimization will substantially improve the Qvalues, and will stimulate the progress on photonic devices for the visible and ultraviolet spectral region. This suggestion was confirmed by further developments demonstrating PC cavities with quality factor as high as 1743 [53], 1800 [85], 4300 [60], 5200 [52], and 5400 [59]. As mentioned above, theoretical calculations indicated a Qfactor of about 4 × 10 4 for a L7 cavity [51].…”
Section: Photonic Applicationssupporting
confidence: 61%
See 2 more Smart Citations
“…It was found that the fabricated membranes exhibit resonant modes with Q = 300, and it was suggested that further design and process optimization will substantially improve the Qvalues, and will stimulate the progress on photonic devices for the visible and ultraviolet spectral region. This suggestion was confirmed by further developments demonstrating PC cavities with quality factor as high as 1743 [53], 1800 [85], 4300 [60], 5200 [52], and 5400 [59]. As mentioned above, theoretical calculations indicated a Qfactor of about 4 × 10 4 for a L7 cavity [51].…”
Section: Photonic Applicationssupporting
confidence: 61%
“…Nonpolar GaN PC H 2 nanocavities with a high quality factor of approximately 4300 at 388 nm were realized at 77 K on a thin membrane structure [60]. The degree of polarization of the emission from this nonpolar GaN PC nanocavity was measured to be 64% along the m crystalline direction, as deduced from data presented in Figures 16a-16c.…”
Section: Properties Of Gan Membrane Structuresmentioning
confidence: 77%
See 1 more Smart Citation
“…Despite such losses, a seven-fold improvement in optical Q factor and order of magnitude decrease in propagation loss at 1550 nm is observed in single crystal GaN devices as compared to our previous GaN-on-silicon platform 20 as well as considerable improvements in optical Q factor compared to recent GaN photonic crystal resonators. [28][29][30] Of the undercoupled telecom C-band devices shown in Figure 2(d), GaN devices exhibited loaded Q factors in excess of 60 000 in devices 1.2 lm and above in width. Such devices exhibited extinction of 3 dB, suggesting that observed Q factors lie near their intrinsic values.…”
mentioning
confidence: 95%
“…In this letter, the nonpolar a-plane GaN-based photonic crystals with different defect nano-cavities have been fabricated. The patterns were defined by an e-beam lithography (EBL) system and the thin membrane structures of the PC defect cavities were fabricated by using the focused ion beam (FIB) milling technique [30][31][32]. Via a micro-photoluminescence (μ-PL) system operated at 77 K, the light emission from the PC defect cavities has been characterized and demonstrated with high Q values in the light emission performance.…”
Section: Introductionmentioning
confidence: 99%